Analysis of Nahwu Errors in Arabic Textbooks at Madrasah Aliyah Negeri 2 Payakumbuh: تحليل الأخطاء النحوية في الكتاب المدرسي للّغة العربية في المدرسة الثانوية الإسلامية الحكومية 2 باياكومبوه - Aini, Syarifah; Arman Husni (Ukazh : Journal of Arabic Studies, 2026)
The main problem of this study is the presence of errors related to nahwu in the Arabic language textbook used by twelfth-grade students at MAN 2 Payakumbuh. This topic was chosen due to the importance of nahwu accuracy, as it significantly affects students’ understanding, particularly in terms of tarkīb and i‘rāb. This study aims to identify the types of nahwu errors found in the textbook, focusing on two main aspects: tarkīb and i‘rāb, and to analyze the factors contributing to these errors. The research employs a library research design with a qualitative approach, using content analysis techniques on sentences and language examples presented in the textbook. The findings indicate two major categories of nahwu errors, namely tarkīb errors and i‘rāb errors. A total of 13 errors were identified in the tarkīb aspect and 11 errors in the i‘rāb aspect. These errors are likely influenced by Indonesian language interference and the inaccurate application of nahwu rules. The study concludes that revisions and improvements to the nahwu content are necessary to ensure conformity with the rules of tandard Arabic (fuṣḥā).